19-(Benzyloxy)-19-oxojolkinolide B (19-BJB), an ent-abietane diterpene diepoxide, inhibits the growth of bladder cancer T24 cells through DNA damage. - Ke Wang; Juan-Cheng Yang; Yeong-Jiunn Jang; Guan-Yu Chen; Ya-Jing Zhang; Yun-Hao Dai; Da-Yong Zhang; Yang-Chang Wu (PLoS ONE, 2021)
Diterpenoids jolkinolide A and B, were first isolated from Euphorbia fischeriana. In our previous research, 19-(Benzyloxy)-19-oxojolkinolide B (19-BJB), a derivative of jolkinolides, was synthesized as a novel ent -abietane diterpene diepoxide. In this study, 19-BJB showed strong in vitro activity against bladder cancer cell lines. DNA damage which was observed through the interaction of 19-BJB with nucleotide chains and affected DNA repair resulted in the activation of checkpoint kinase 1 (Chk1) and checkpoint kinase 2 (Chk2) in bladder cancer cell lines. In vivo testing in nude mice also proved that 19-BJB revealed a potential inhibitory effect on tumor growth. Additionally, the 3D-QSAR models of jolkinolides were established. Briefly, we proved that 19-BJB could potentially be used as a drug to inhibit the growth of bladder tumor.